2014
DOI: 10.1080/09588221.2014.960941
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an ICALL tutoring system and process-oriented corrective feedback

Abstract: A Web-based form-focused intelligent computer-assisted language learning (ICALL) tutoring system equipped with a process-oriented corrective feedback function was developed to investigate the extent to which such a program may serve as a viable method of teaching grammar to Korean secondary and elementary students. The present study was also intended to explore the overall efficacy of two different types of corrective feedback on errors made by students while using the process-oriented tutoring program. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 52 publications
1
34
1
Order By: Relevance
“…These high mean values, the positive comments, and the significant relationship of At and EE with BI indicate not only that MyST is accepted by its target users, but also that they enjoy it and find it useful and easy to use. This is in contradiction with findings by Choi (2016), who suggested that even the most advanced neuro-linguistic programme technology is not capable of adequately examine learners' output and thus may cause frustration and reduce motivation. Since users of the ASR-based CALL system MyST were positive, MyST seems suitable to carry out more research.…”
Section: Discussioncontrasting
confidence: 83%
“…These high mean values, the positive comments, and the significant relationship of At and EE with BI indicate not only that MyST is accepted by its target users, but also that they enjoy it and find it useful and easy to use. This is in contradiction with findings by Choi (2016), who suggested that even the most advanced neuro-linguistic programme technology is not capable of adequately examine learners' output and thus may cause frustration and reduce motivation. Since users of the ASR-based CALL system MyST were positive, MyST seems suitable to carry out more research.…”
Section: Discussioncontrasting
confidence: 83%
“…Choi (2014) suggested that even the most advanced neuro-linguistic programme technology does not adequately examine EFL learners' output, which may cause frustration and reduce motivation. Furthermore, although CALL may facilitate EFL learners' autonomous learning, such learning is not sustainable without teachers' guidance.…”
Section: Discussionmentioning
confidence: 98%
“…Choi [96] developed a web-based ITS equipped with a process-oriented corrective feedback function and found that it may facilitate EFL learners' acquisition of grammatical concepts. The majority of participants showed favorable perceptions of the tutoring program.…”
Section: Intelligent Tutoring System (Its)mentioning
confidence: 99%